2018
DOI: 10.22146/jae.23013
|View full text |Cite
|
Sign up to set email alerts
|

Supply Response Analysis Of Paddy In Kediri : Managerial Implications

Abstract: Research of farmer's response analysis to price is important to increase paddy production in Kediri. Farmers are conducted as the object of the research because they are the decision INTISARIPenelitian analisis respon petani terhadap harga penting untuk meningkatkan produksi padi di Kediri. Petani diperlakukan sebagai objek penelitian karena mereka adalah pengambil keputusan pada semua kegiatan bertani. Penelitian ini bertujuan untuk mengetahui pengaruh respon panen, respon produktivitas, respon penawaran padi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…After we obtained the environmental efficiency of sample firms based on SBM-DEA, we used the regression model to analyze the determinants of environmental efficiency of sample firms as a second stage. As the residuals' expected value is necessarily zero in the OLS hypothesis, it may yield inconsistent or biased estimates when applying OLS on censored or truncated data [29]. Especially since the value of efficiency measures is between 0 and 1 in the SBM-DEA model with undesirable output, the traditional OLS estimation is not favorable for testing the determinants of environmental efficiency [15].…”
Section: Tobit Regression Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…After we obtained the environmental efficiency of sample firms based on SBM-DEA, we used the regression model to analyze the determinants of environmental efficiency of sample firms as a second stage. As the residuals' expected value is necessarily zero in the OLS hypothesis, it may yield inconsistent or biased estimates when applying OLS on censored or truncated data [29]. Especially since the value of efficiency measures is between 0 and 1 in the SBM-DEA model with undesirable output, the traditional OLS estimation is not favorable for testing the determinants of environmental efficiency [15].…”
Section: Tobit Regression Modelmentioning
confidence: 99%
“…Y np = the explained variable, x np = the explanatory variable, β T = the vector of the regression coefficient of the explanatory variable, np = the stochastic error assumed to follow the distribution of N(0, σ 2 ), respectively. To assess the factors influencing inefficiency in agriculture and its related sectors, the Tobit model can be defined in Equation ( 4) as [29]:…”
Section: Tobit Regression Modelmentioning
confidence: 99%
“…Some studies on paddy supply response have been conducted. A study in Kediri showed that the supply response of paddy harvest area to the area of paddy harvest in the previous year was inelastic in the short and long run (Choirina et al, 2016), while the supply response of local rice in Nigeria indicated that in the short-run supply response of local rice production to the expected price of local rice and area planted with local rice was inelastic, but in the longrun it became elastic (Rahji & Adewumi, 2008). Another study was conducted concerning the supply response of maize in Pakistan (Khan et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Supply response can be approached by using the harvested area of a commodity. The research in Kediri used an approach to harvest area of paddy to determine the supply response of rice (Choirina et al, 2016). The study used the variables of price of rice, fertilizer price index, rainfall, rice harvest area at 1, 2 and 3 years earlier.…”
Section: Introductionmentioning
confidence: 99%